Obesity Risk in Children: The Role of Acculturation in the Feeding Practices and Styles of Low-Income Hispanic Families - Power, Thomas G. (Child Obes, 2015)
Background: Parent feeding has been associated with child overweight/obesity in low-income families. Because acculturation to the United States has been associated with increased adult obesity, our study aim was to determine whether acculturation was associated with feeding in these populations. Methods: Low-income Hispanic mothers of preschoolers were recruited to participate in a longitudinal study examining child eating behaviors. At baseline, mothers completed questionnaires on feeding styles, feeding practices, and acculturation. Regression analyses compared feeding styles and food parenting practices of first-generation, immigrant mothers born outside the United States (n = 138) and mothers born in the United States (n = 31). The correlates of acculturation with these same constructs were also examined. Results: Immigrant mothers reported using highly directive food parenting practices more often than mothers born in the United States, including pressuring their child to consume more food, using food as a reward, and controlling child food intake by limiting less-healthy foods. First-generation mothers were more likely to show authoritarian, and less likely to show indulgent, feeding styles. Greater maternal acculturation was associated with less restriction of food for weight reasons. Conclusions: Although first-generation, immigrant mothers reported using highly controlling food parenting practices with their children, those born in the United States were more indulgent with their children in the feeding context. Mechanisms that promote greater indulgence in more-acculturated mothers need to be identified.